2005
DOI: 10.1002/sce.20086
|View full text |Cite
|
Sign up to set email alerts
|

Haptic augmentation of science instruction: Does touch matter?

Abstract: This study investigated the impact of haptic augmentation of a science inquiry program on students' learning about viruses and nanoscale science. The study assessed how the addition of different types of haptic feedback (active touch and kinesthetic feedback) combined with computer visualizations influenced middle and high school students' experiences. The influences of a PHANToM (a sophisticated haptic desktop device), a Sidewinder JONES ET AL.(a haptic gaming joystick), and a mouse (no haptic feedback) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 22 publications
4
91
0
1
Order By: Relevance
“…In biology, Jones, Minogue, Tretter, Negishi, and Taylor (2006) explored the use of haptic virtual models in students' interpretation of viruses. In a further study on learning with a 3D haptic virtual model of an animal cell, Minogue, Jones, Broadwell, and Oppewall (2006) found that haptic experiences improved students' ability to navigate and interpret the cell environment.…”
Section: Students' Interaction and Learning With Haptic Virtual Modelmentioning
confidence: 99%
“…In biology, Jones, Minogue, Tretter, Negishi, and Taylor (2006) explored the use of haptic virtual models in students' interpretation of viruses. In a further study on learning with a 3D haptic virtual model of an animal cell, Minogue, Jones, Broadwell, and Oppewall (2006) found that haptic experiences improved students' ability to navigate and interpret the cell environment.…”
Section: Students' Interaction and Learning With Haptic Virtual Modelmentioning
confidence: 99%
“…In addition, some researchers have explored the effect of haptic augmentation of instruction on size and scale understandings [23,24]. For example, Jones et al [23] found that students in both limited-haptic and full-haptic environments made significant gains in their understandings of nanometer scale.…”
Section: Additional Influences On Conceptions Of Size and Scalementioning
confidence: 99%
“…Specifically, students in both treatment groups were more likely to identify examples of nano-sized objects and describe the degree to which a human would have to be shrunk to reach the size of a virus. In another study examining the influence of haptic augmentation on science learning, Jones et al [24] found that students who were given the opportunity to actively "touch" the viruses via haptic feedback appeared to be more interested and engaged in the educational experience. Also, the students' use of analogies increased with the use of a haptic desktop device, suggesting that this learning environment may influence the way in which the students construct their understandings about abstract science concepts.…”
Section: Additional Influences On Conceptions Of Size and Scalementioning
confidence: 99%
“…Recent work on learning in virtual environments in a nano-context has focused on letting users interact with simulations of advanced equipment such as atomic force microscopy [5,6]. However, apart from a few examples (e.g.…”
Section: Framing the Problemmentioning
confidence: 99%